Perlindungan Hukum bagi Kreditor dalam Pendaftaran Jaminan Fidusia apabila Debitor Wanprestasi - suphia suphia (Fakultas Hukum Universitas Islam Jember, 2014)
Fiduciary registration is the most important stages in the fiduciary is a fiduciary because the birth date on record according to the fiduciary Fiduciary Book List. The position of the creditors as a fiduciary are in a weak position when a loan has been disbursed to the debtor as a fiduciary giver. Creditors require certainty and legal protection for unpaid credit guarantee has been received by the debtor. Legal protection is very necessary when the debtor does not fulfill its obligations (default) to repay the loan in accordance with the agreed time.